Práticas de gestão sustentável de recursos humanos e seus impactos nos danos à saúde relacionados ao trabalho e no comprometimento organizacional - Genari, Denise (My University, 2018)
Purpose: To identify the practices of sustainable human resources management and their impacts on health harm of work and organizational commitment. Thesis declaration: Sustainable human resources management practices favor the reduction of health harm of work and the increase of organizational commitment. Methodology: A qualitative research phase was developed to contextualize the integration of human resources management and sustainability, involving a sample comprised of companies classified in the Bovespa Sustainability Index 2016/2017. Subsequently, using descriptive research, a quantitative phase was carried out, based on a survey involving the participation of 290 employees of the said companies, in order to identify the variables related to the practices of sustainable human resources management and to test the proposed relations by using structural equation modeling. Findings: The results indicate that the practices of sustainable human resources management are represented by three dimensions: the attraction and retention of professionals, the maintaince of healthy and motivated professionals and the development of the professionals’ skills. In addition, these practices have a significant and negative impact on health harm of work, which are shown by the risk factors for psychological health, by the restrictions for positive health, and by the side effects of work. It was also apparent that the practices of sustainable human resources management have a significant and positive impact on affective and normative commitment, and the affective commitment stands out as a partial mediator of the relationship between the practices and the normative commitment. Practical implications: With regard to academic contributions, the present study enabled the empirical and comprehensive evaluation of the variables related to sustainable human resources management practices and their consequent elements, in convergence with the research agenda of the management field, which focuses on the results for the individuals(employees) and for the organizations. Gerencial implications: The identification and possible application of certain practices of sustainable human resources management as a way to minimize the damages to the health harm of work and to encourage the commitment are established with the main managerial contribution.
Objetivo: Identificar as práticas de gestão sustentável de recursos humanos e os seus impactos nos danos à saúde relacionados ao trabalho e no comprometimento organizacional. Declaração de tese: As práticas de gestão sustentável de recursos humanos impactam na redução dos danos à saúde relacionados ao trabalho e no aumento do comprometimento organizacional. Procedimentos metodológicos: Desenvolveu-se uma etapa qualitativa de pesquisa, com o objetivo de contextualizar a integração da gestão de recursos humanos e da sustentabilidade, em uma amostra de empresas classificadas no Índice Bovespa de Sustentabilidade 2016/2017. Na sequência, com cunho descritivo, realizou-se uma etapa quantitativa, baseada em uma survey, com a participação de 290 funcionários das referidas empresas, com o intuito de identificar as variáveis que representam as práticas de gestão sustentável de recursos humanos e testar as relações propostas, por meio da utilização de modelagem de equações estruturais. Principais resultados: Os resultados apontam que as práticas de gestão sustentável de recursos humanos são representadas por três dimensões: atração e retenção de profissionais, manutenção de profissionais motivados e saudáveis e desenvolvimento das competências dos profissionais. Além disso, as referidas práticas possuem um impacto significativo e negativo nos danos à saúde relacionados ao trabalho, que são retratados pelos fatores de risco para a saúde psicológica, pelas restrições para um estado de saúde positivo e pelos efeitos colaterais do trabalho. Também se verificou que as práticas de gestão sustentável de recursos humanos impactam de maneira significativa e positiva no comprometimento afetivo e normativo, sendo que o comprometimento afetivo se destaca como um mediador parcial da relação entre as práticas e o comprometimento normativo. Implicações teóricas: No que diz respeito às contribuições acadêmicas, o presente estudo possibilitou a avaliação empírica e abrangente das variáveis vinculadas às práticas de gestão sustentável de recursos humanos e seus elementos consequentes, em convergência com a agenda de pesquisas do campo da gestão, que enfoca os resultados para os indivíduos (funcionários) e para as organizações. Implicações gerenciais: A identificação e a possível aplicação de determinadas práticas de gestão sustentável de recursos humanos como uma forma de minimizar os danos à saúde relacionados ao trabalho e fomentar o comprometimento se estabelecem com a principal contribuição gerencial.
Keywords: Saúde e trabalho; Sustentabilidade; Administração de pessoal; Comprometimento organizacional; Health and work; Sustainability; Personnel management; Organizational commitment